Do Store Brands Aid Store Loyalty? - Seenivasan, Satheesh; Sudhir, K.; Talukdar, Debabrata (Management Science, 2016)
Do store brands aid store loyalty by enhancing store differentiation or merely draw price-sensitive customers with little or no store loyalty? This paper seeks to answer this question by empirically investigating the relationship between store brand loyalty and store loyalty. First, we find a robust, monotonic, positive relationship between store brand loyalty and store loyalty by using multiple loyalty metrics and data from multiple retailers and by controlling for alternative factors that can influence store loyalty. Second, we take advantage of a natural experiment involving a store closure and find that the attrition in chain loyalty is lower for households with greater store brand loyalty prior to store closure. Together, our results are consistent with evidence for the store differentiation role of store brands. This paper was accepted by J. Miguel Villas-Boas, marketing.